Food and Agricultural Product Industry as the Economic Defence for Indonesia's COVID-19 Economic Crisis [Industri Produk Pangan dan Tani sebagai Pertahanan Ekonomi untuk Krisis Ekonomi di Indonesia selama Pandemi COVID-19] - Roy Vincentius Pratikno; Jhon Maxwell Yosua Pattinussa (Universitas Pelita Harapan, 2022)
The global economic crisis as a result of the COVID-19 pandemic has become one of the worst crises in the current era of the integrated modern economy. The decline in GDP and economic growth in almost all countries was forced to experience negative contractions throughout 2020. The paralysis of the manufacturing industry and the obstruction of the global production chain became one of the main causes of the crisis. All countries in the world are forced to re-evaluate and look again at the right solution amid international trade uncertainty. Indonesia, which is still dependent on the manufacturing industry, is forced to look for other solutions that can be applied in this situation. By prioritizing agricultural and food products, Indonesia has managed to get out of the economic crisis of the COVID-19 pandemic. Therefore, this paper aims to identify the government's decision to make agricultural and food products the spearhead of the national economy. Using a qualitative approach, and focusing on identifying solutions for the agriculture and food industry, the research team tried to look at the economic logic in international and national contexts. In this paper, the researcher’s team agreed that Porter's Diamond theory can be used as a reference for the based framework because it is considered to be able to explain in detail the relationship between government decisions and changes that occur amid modern international trade uncertainty.Bahasa Indonesia Abstract: Krisis ekonomi global akibat dari pandemi COVID-19 menjadi salah satu krisis terparah di era ekonomi modern teritegrasi saat ini. Penurunan GDP dan pertumbuhan ekonomi hampir di seluruh negara terpaksa harus mengalami kontraksi negatif sepanjang tahun 2020 silam. Kelumpuhan industri manufaktur dan terhambatnya rantai produksi global menjadi salah satu penyebab utama krisis tersebut. Seluruh negara di dunia terpaksa untuk kembali melakukan evaluasi dan melihat kembali bagaimana solusi yang tepat di tengah ketidakpastian perdagangan internasional. Termasuk Indonesia yang masih bergantung dengan industri manufkatur terpaksa mencari solusi lain yang dapat diterapkan dalam kedaan ini. Dengan mengedepankan produk pertanian dan pangan Indonesia berhasil keluar dari keterpurukan krisis ekonomi pandemi COVID-19. Maka dari itu, tulisan ini bertujuan untuk memberikan identifikasi terhadap keputusan pemerintah yang menjadikan produk tani dan pangan sebagai ujung tombak perekonomian nasional. Dengan menggunakan pendekatan kualitatif, dan berfokus kepada identifikasi solusi industri tani dan pangan, tim peneliti mencoba untuk melihat logika ekonomi dalam konteks internasional dan nasional. Dalam penyusunan tulisan ini, tim penulis sepakat bahwa teori Porter’s Diamond bisa digunakan sebagai acuan pikir dalam tulisan, karena dinilai dapat menjelaskan secara mendetail mengenai hubungan antara keputusan pemerintah dan perubahan yang terjadi di tengah ketidakpastian perdagangan internasional modern.